The Trial of repetition in the face of the unjustified delay in the contentious administrative processes - Loor Párraga, Jeniffer Julliet; Reyna Zambrano, María Yokir (Frónesis, 2022)
This paper contains a doctrinal and legal analysis of the unjustified delay in the administration of justice and its incidence in the State paying large amounts of money in administrative contentious processes, with the aim of justifying who should answer in the trial of repetition by the amount is generated due to the delay in processing and executing a judgment in these court cases. Considering that in Ecuador, it is well known that administrative litigation courts are overburdened by the procedure overload, which will lead to delays and thus increase the economic compensation in these procedures, so what is the relevance? The research is developed through the legal theoretical method that implies a normative study with doctrinal elements of the right of repetition, the unjustified delay in the administration of justice, and economic reparation within the framework of Administrative Law.